PENERAPAN FILOSOFI DESAIN ARSITEK ANDRA MATIN PADA AM RESIDENCE - Nicholas -; Caecilia S. Wijayaputri (Riset Arsitektur (RISA), 2023)
Abstract - Design philosophy is an abstraction of determining a character in architectural design. Tolearn and apply the design philosophy to be designed or made, it is necessary to have good parameters or rolemodels in order to create or determine your own design philosophy. One of the architects who has an interestingdesign philosophy and way of designing is architect Andra Matin, where when you see the building he designed,you can feel and see that the building has its own character.The object of study that is considered quite interesting to study is the house of Andra Matin itself,namely AM Residence. AM Residence was chosen because the house is a house that Andra Matin designedwithout any interference from other parties, or it can be said that all ideas or applications of his designphilosophy can be fully implemented there.This research begins by analyzing first who Andra Matin is and what his design philosophy is, then heconducts an interview with Andra Matin. After getting the results from interviews and observing the designphilosophy, a 3D redesign of the building was made, then an analysis was carried out on how to apply AndraMatin's design philosophy to AM Residence, and cross-checked with the theory of form, space, andarrangement from D.K. ching.The purpose of this study is to find out how and also the application of his own design philosophy indesigning a building. After knowing the application of this philosophy will make architecture students have theright starting point in starting an architectural career.Keywords: Andra Matin, Architecture, Design Philosophy.